Dissolution and Solubility of the Synthetic Natroalunite and the Arsenic-Incorporated Natroalunite at pH of 2.00–5.60 and 25–45°C. (3rd November 2019) - Zhu, Yinian; Xuan, Huiling; Liang, Yanpeng; Yan, Qiming; Zhu, Zongqiang; Jiang, Zhangnan; Zhang, Lihao; Liu, Huili; Tang, Shen
Abstract : Arsenic is very harmful to most living organisms. The solubility data of As-containing compounds are significant in geoscience and environmental science. The arsenic-incorporated natroalunite precipitation has been proposed to eliminate arsenic from water, both for industrial practice and remediation of polluted areas. Unfortunately, only few works have been made on partial arsenic incorporation in natroalunite and the thermodynamic data for natroalunite and arsenic-incorporated natroalunite now are still lacking. Moreover, the dissolution mechanisms of arsenic-incorporated natroalunites have never been studied. In the present work, the dissolution of the synthetic natroalunite [Na0.93 (H3 O)0.61 Al2.82 (SO4 )2 (OH)6 ] and the synthetic arsenic-incorporated natroalunite [Na0.88 (H3 O)2.44 Al2.35 (AsO4 )0.38 (SO4 )1.62 (OH)6 ] at 25°C, 35°C, and 45°C was experimentally examined in HNO3 solution (pH of 2.00 and 4.00) and pure water. The characterizations confirmed that the solids showed no recognizable change after dissolution. All dissolutions underwent a pH variation, which was caused by a great depleting of H3 O + /OH − ions, typically at the reaction beginning. The dissolution in H3 O + medium proved to be near-stoichiometric within the short beginning period, and the dissolved Na +, Al 3+, SO4 2−, and AsO4 3− concentrations were stoichiometric according to the initial solids and then appeared to be nonstoichiometric with the Na/SO4 mole ratios higher and the Al/SO4 and AsO4 /SO4 mole ratios lower than the stoichiometry until the experimental end, indicating that the components were released from solid to solution preferentially after the following order: Na + (H3 O + ) > SO4 2− > AsO4 3− > Al 3+ . From the experimental results under the condition of initial pH 2.00 and 25°C, the solubility products [ K sp ] and the Gibbs free energies of formation [Δ G f ° ] were calculated to be 10 −81.02±0.33 ∼10 −81.04±0.27 and −4713 ± 2 to −4714 ± 1 kJ/mol for the natroalunite and 10 −92.30±0.30 ∼10 −92.41±0.37 and −5078 ± 2 to −5079 ± 2 kJ/mol for the arsenic-incorporated natroalunite, respectively. The thermodynamic quantities, Δ G °, Δ H °, Δ S °, and Δ C p °, were determined to be 462303.43 J/K·mol, 122466.83 J/mol, −1140.39 J/K·mol, and 4280.13 J/K·mol for the natroalunite dissolution reaction at initial pH 2.00 and 25°C and to be 526925.48 J/K·mol, 159674.76 J/mol, −1232.38 J/K·mol, and 1061.12 J/K·mol for the dissolution of the arsenic-incorporated natroalunite at initial pH 2.00 and 25°C, respectively.